Genome-wide identification and expression analysis of the PsKIN gene family in pea - Yuan, Hao; Liu, Baoxia; Zhang, Guwen; Feng, Zhijuan; Wang, Bin; Bu, Yuanpeng; Xu, Yu; Gong, Yaming; Sun, Zhihong; Liu, Na (Frontiers in Genetics, 2024)
Peas (Pisum sativum L.) serve as a vital model for plant development and stress research. The kinesin (KIN) gene family, encoding essential motor proteins, remains understudied in peas. Our research conducted a comprehensive genomic analysis of the KIN genes in peas, identifying 105 genes categorized into seven subfamilies based on evolutionary relationships, gene structures, conserved motifs, and interaction networks. A comparative analysis with Arabidopsis and soybean KIN gene families showed a non-uniform distribution of PsKIN genes across subfamilies. Homology analysis revealed that the PsKIN family has undergone segmental duplication and is under negative selection pressures, with conserved genes on chromosomes Ps5, Ps6, and Ps7 playing a significant role in pea evolution. Transcriptomics revealed 38 PsKIN genes with distinct tissue-specific expression, with PsKIN76, PsKIN96, PsKIN82, and PsKIN103 showing significant levels in roots, lateral roots, stems, petals, and seeds, respectively. Differential expression under drought and saline stress was observed, with PsKIN8, PsKIN11, PsKIN54 upregulated under drought, and PsKIN47 and PsKIN51 under saline stress. These genes are potential candidates for improving plant stress tolerance. This study offers insights into the pea KIN gene family, highlighting their potential in enhancing plant stress tolerance and setting a stage for future research.